2020
DOI: 10.3390/land9060195
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Ecosystem Services in Constituting Multi-Functional Landscapes in Slovakia

Abstract: Landscape provides many services for human wellbeing through its mosaic of ecosystems. Although different landscape spatial structures limit some access to these services for local residents, their demand for landscape benefits creates a crucial component in landscape planning. Herein, we evaluate the ecosystem service supply from landscape structures in four different areas of Slovakia and we identify the public preferences for these services. This evaluation was assisted by expert-based ecosystem services (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 70 publications
0
5
1
Order By: Relevance
“…analysis revealed that, with the exception of noise abatement ES, spatially explicit ES mismatches have no signi cant correlation with Singapore residents' perception towards ES importance. This contradicts previous perception-based studies in the cases of Indonesia(Muhamad et al, 2014), Ecuador(Aguado et al, 2018) and Slovakia(Bezák et al, 2020), which suggested the signi cance of one's lived experiences of unmet ES demand or absence of ES supply in heightening ES awareness and perception.In particular, the positive correlation between the mismatch value of noise abatement ES at 400m and its importance rating, runs directly opposite to this reasoning. It implies that people who experience a more negative mismatch, value the ES less; while those who experience a more positive mismatch, value it more.…”
contrasting
confidence: 75%
“…analysis revealed that, with the exception of noise abatement ES, spatially explicit ES mismatches have no signi cant correlation with Singapore residents' perception towards ES importance. This contradicts previous perception-based studies in the cases of Indonesia(Muhamad et al, 2014), Ecuador(Aguado et al, 2018) and Slovakia(Bezák et al, 2020), which suggested the signi cance of one's lived experiences of unmet ES demand or absence of ES supply in heightening ES awareness and perception.In particular, the positive correlation between the mismatch value of noise abatement ES at 400m and its importance rating, runs directly opposite to this reasoning. It implies that people who experience a more negative mismatch, value the ES less; while those who experience a more positive mismatch, value it more.…”
contrasting
confidence: 75%
“…• ES and indicators were identified relevant to actual land-use activities in the local context: the multifunctionality of land-use systems can be considered [94,95].…”
Section: Advantage Challengementioning
confidence: 99%
“…Yet this can be problematic if top-down agendas do not meet local needs and perspectives, especially if the settings of financial and legal frameworks for the policy implementation are questionable (Konečný et al, 2021). Despite the fact that rural areas are often seen as important mainly in the local and regional context, their ability to provide ecosystem services and contribute to climate change mitigation and adaptation makes them important actors with large sustainability potential even at the global level (Bezák et al, 2020). Therefore, our main research objective is to identify how LAGs perceive various strategies related to sustainable development, how they reflect the importance of the SDGs for their region, and how they anticipate their own contribution to the SDGs' fulfillment in the local circumstances.…”
Section: Introductionmentioning
confidence: 99%